Cultivating Demand for the Arts Arts Learning, Arts Engagement, and State Arts Policy - Zakaras, Laura (RAND Corporation, 2008)
What does it mean to cultivate demand for the arts? Why is it important and necessary to do so? What can state arts agencies and other arts and education policymakers do to make it happen? The authors set out a framework for thinking about supply and demand in the arts and identify the roles that different factors, particularly arts learning, play in increasing demand for the arts.